Carbon-based composite conductive material, heating element and application of carbon-based composite conductive material in cigarette heating
By generating metal nanoparticles in situ on carbon-based composite conductive materials and combining them with a thermally conductive insulating layer and an interface coating, the problems of oxidation, uneven thermal conductivity, and inaccurate temperature control in traditional heated cigarette elements are solved. This achieves rapid heating, precise temperature control, and stable aerosol release, thus extending the service life of the heating element.
Patent Information
- Application Number
- CN202511155606.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-11-28
AI Technical Summary
Traditional heated cigarettes use metal and ceramic heating elements that suffer from problems such as oxidation, low thermal conductivity, uneven heating, inaccurate temperature control, and short lifespan, making it difficult to meet the requirements for rapid response and stable aerosol release.
By using carbon-based composite conductive materials, metal nanoparticles are generated in situ on the carbon-based conductive composite network structure material, and combined with a thermally conductive insulating layer and an interface coating to form a heating element, rapid heating and precise temperature control can be achieved.
It achieves rapid heating of heating elements, precise temperature control, stable release of aerosol components, and extended service life, meeting the requirements for improving the performance and quality of heated cigarettes.
Smart Images

Figure CN121014940A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of heated cigarette technology, specifically to a carbon-based composite conductive material, a heating element, and its application in heated cigarettes. Background Technology
[0002] In traditional heated cigarette technology, metal sheets (such as nickel-chromium alloys) and ceramic heating elements are common heating components. When energized, they utilize the Joule effect to generate heat and heat the tobacco cartridge. While these heating elements offer advantages such as a large heat transfer surface and high heating efficiency, they suffer from several problems in practical applications. Metal elements are prone to oxidation, leading to resistance drift over time and consequently, inaccurate temperature control. Furthermore, limitations imposed by material anisotropy and structural design can cause localized high-temperature zones during heating, resulting in uneven heating of the tobacco core material and affecting the smoking experience and consistency. Ceramic materials have low thermal conductivity and slow heating rates, typically requiring more than 10 seconds to reach the desired temperature of 250°C. Metal oxide layer peeling and ceramic microcrack propagation cause traditional elements to experience a thermal efficiency decrease of over 15% after more than 200 heating cycles, and they also struggle to meet the demands for rapid temperature response. Therefore, developing a composite heating element based on the Joule heating effect to achieve precise temperature control, stable release of aerosol components, sensitive response, and improved element lifespan is crucial for enhancing the performance and quality of heated cigarettes. Summary of the Invention
[0003] In view of this, the main objective of this invention is to provide a method for preparing a carbon-based composite conductive material. This method mainly involves the in-situ generation of metal nanoparticles on a composite network structure material, and the conductivity of this conductive material can reach 1.0 × 10⁻⁶. 5 S / cm~2.0×10 5 With a thermal conductivity of 327 W / (m·K) to 1168 W / (m·K), it can be used as a conductive heating core material in heating elements, exhibiting high Joule thermal efficiency and fast heat transfer rate.
[0004] To achieve the above objectives, the present invention provides a method for preparing a carbon-based composite conductive material, comprising the steps of: firstly pre-oxidizing the carbon-based conductive composite network structure material; then immersing it in a metal salt solution and reducing it in situ under an inert gas environment to form metal nanoparticles, thereby obtaining a carbon-based conductive composite material modified with metal nanoparticles.
[0005] Furthermore, the purpose of the pre-oxidation treatment is to improve surface hydrophilicity, provide reaction sites, and enhance the bonding force between metal nanoparticles and the carbon-based conductive composite network structure material. Specifically, the pre-oxidation treatment includes pre-oxidizing the carbon-based conductive composite network structure material in a mixed atmosphere at 180℃ to 320℃ for 2 h to 5 h; wherein the mixed atmosphere mainly consists of oxygen and nitrogen, and the oxygen volume accounts for 10% to 25%. Alternatively, the pre-oxidation treatment can also employ an oxidant to oxidize the carbon-based conductive composite network structure material.
[0006] Furthermore, to ensure that the metal salt solution uniformly and fully impregnates the carbon-based conductive composite network structure material, the carbon-based composite conductive material has relatively high Joule thermal efficiency and heat transfer efficiency. The porosity of the carbon-based conductive composite network structure material is 0.5%–50%, preferably 30%–50%; the conductivity of the carbon-based conductive composite network structure material is 1000 S / cm–100000 S / cm, preferably 10000 S / cm–25000 S / cm; the concentration range of the metal salt solution is 2 wt%–50 wt%; the impregnation time is 0.5–6 h; and the metal salt solution also contains at least one soluble salt of the following metals: Ag, Cu, Al, Ni, Zn, Ti, Co, Rh, Pt, Fe, Pd, Zr, that is, the metal nanoparticles include one or more of Ag, Cu, Al, Ni, Zn, Ti, Co, Rh, Pt, Fe, Pd, and Zr; the in-situ reduction reaction time is 1 h–3 h.
[0007] Thus, the metal nanoparticles fill 5% to 50% of the carbon-based conductive composite network structure material, meaning that the metal nanoparticles fill the pores of the carbon-based conductive composite network structure material, and the filling volume is 5% to 50% of the total pore volume in the material.
[0008] The carbon-based conductive composite network architecture material includes one or more porous materials with a three-dimensional network structure, such as multilayer graphene, carbon fibers, and carbon nanotubes. The carbon fibers can be pitch-based carbon fibers, viscose-based carbon fibers, or vapor-grown carbon fibers, etc.
[0009] Preferably, the carbon-based conductive composite network structure material is a graphene self-supporting membrane with a porosity of 30% to 50%, which is mainly prepared by filtration of graphene dispersion. The filling degree of the metal nanoparticles in the graphene self-supporting membrane is 21.6% to 28.4%, which can increase the conductivity of the graphene self-supporting membrane by 11.2% to 18.5%.
[0010] The second objective of this invention is to provide a carbon-based composite conductive material prepared by the above-described method, wherein metal nanoparticles are modified on a pre-oxidized carbon-based conductive composite network structure material by an in-situ reduction method, thereby making the metal nanoparticles tightly bonded to the carbon-based conductive composite network structure material and effectively improving the conductivity and thermal conductivity of the carbon-based / metal composite material.
[0011] A third objective of this invention is to provide a heating element based on the Joule heating effect. Utilizing the aforementioned carbon-based composite conductive material as the core component of this heating element, electrical energy can be rapidly converted into heat energy. The Joule heating effect is achieved through excellent electrical conductivity, increasing the heating rate of the element and enabling a temperature of 300°C to be reached within 5 seconds. This element can be used as a heating element for heating cigarettes. Specifically, a heating element based on the Joule heating effect includes: a conductive core layer that converts electrical energy into heat energy, and a thermally conductive insulating layer that isolates the conductive core layer from the external environment. The conductive core layer is composed of the aforementioned carbon-based composite conductive material.
[0012] The thermally conductive insulating layer prevents electrical breakdown during heating while providing good thermal diffusion characteristics and mechanical support. It is bonded to the surface of the conductive core layer via laser sintering. The thermally conductive insulating layer has a low coefficient of thermal expansion, especially a low average coefficient of thermal expansion (8 ppm / ℃ to 10 ppm / ℃) during heating from room temperature to 300℃, resulting in minimal impact of deformation on the lamination of the heating element during heating. The thickness of the thermally conductive insulating layer is preferably 0.5 µm to 2 µm. The material of the thermally conductive insulating layer includes one or more of carbon-based ceramic materials, nitrogen-based ceramic materials, and boron-based ceramic materials; wherein the carbon-based ceramic material can be graphite, porous carbon, or silicon carbide; the nitrogen-based ceramic material can be silicon nitride, aluminum nitride, or hexagonal boron nitride; the boron-based ceramic material can preferably be silicon boride or aluminum boride; and the material of the thermally conductive insulating layer is hexagonal boron nitride, aluminum nitride, or silicon nitride.
[0013] Furthermore, the heating element also includes an interface coating to suppress thermal stress delamination between the conductive core layer and the thermally conductive insulating layer. The interface coating coats the outer surface of the thermally conductive insulating layer, primarily ensuring a tight bond between the conductive core layer and the thermally conductive insulating layer, providing high oxidation resistance; additionally, it prevents direct contact between the heated object and the thermally conductive insulating layer, thus avoiding wear. The thickness of the interface coating is preferably 0.05 µm to 2 µm. The interface coating can withstand temperatures of 400 ℃ to 600 ℃ and has good thermal conductivity. The interface coating includes any single layer or any composite coating selected from Al2O3 coating, AlN coating, BN coating, and graphene coating.
[0014] Furthermore, a Pt100 temperature sensor and a PID control circuit are integrated on the interface coating, and the Pt100 temperature sensor and the PID control circuit are electrically connected to the conductive core layer, thereby enabling precise control of the heating temperature of the heating element. A resistance circuit is provided on the conductive core layer, and this resistance circuit is connected to the PID control circuit.
[0015] To adapt to the use of heating elements in different appliances, the processing adaptability of the heating element can meet the needs of application environments with processing morphologies such as ring, sheet, and needle.
[0016] Due to the improved heat transfer efficiency, the heating element involved in this invention has a shorter heating time at the same heating temperature compared to a single ceramic heating element. Therefore, the heating element can achieve efficient heating by utilizing the Joule heating effect while meeting the needs of energy saving and consumption reduction during the heating process.
[0017] A fourth objective of this invention is to provide a method for fabricating the above-mentioned heating element, which is simple and easily industrialized. Specifically, a method for fabricating the above-mentioned heating element includes the steps of: laminating or co-firing the thermally conductive insulating layer onto the conductive core layer, with the layers bonded by laser sintering.
[0018] Furthermore, the above preparation method includes: firstly, depositing the thermally conductive insulating layer material layer by layer onto the surface of the carbon-based composite conductive material by static pressing, dry pressing or photopolymerization 3D printing, and then performing interlayer laser sintering treatment.
[0019] Furthermore, in order to ensure that the thermally conductive insulating layer is fixed to the surface of the conductive core layer and to avoid interlayer delamination during the use of the heating element, a sintering technique is used for lamination. The laser sintering temperature is 1200 ℃~1500 ℃ and the laser sintering time is 15 min~90 min.
[0020] Furthermore, the above preparation method also includes forming an interface coating on the outer surface of the conductive core layer and the thermally conductive insulating layer. The method for forming the interface coating includes magnetron sputtering, plasma spraying, or dip coating, etc.
[0021] Furthermore, the above preparation method also includes: integrating a Pt100 temperature sensor and a PID control circuit on the surface of the interface coating.
[0022] The fifth objective of this invention is to provide an application of the above-mentioned heating element in a tobacco product heater or smoking accessory, which can effectively increase the aerosol release of the heated tobacco product. The heater or heated cigarette accessory is preferably a novel heater or smoking accessory for tobacco products. To adapt to different heaters or smoking accessories, the heating method of the heating element includes center plate heating, center needle heating, and circumferential heating. The thickness of the thermally conductive insulating layer in the heating element is preferably 0.5 µm to 2 µm, and the thickness of the interface coating is preferably 0.05 µm to 2 µm.
[0023] The sixth object of the present invention is to provide a heated cigarette device in which the above-mentioned heating element is installed.
[0024] The seventh objective of this invention is to provide an application of the above-mentioned carbon-based composite conductive material or the above-mentioned heating element in heating cigarettes.
[0025] The carbon-based composite conductive material, heating element, and their application in heated cigarettes described in this invention not only achieve precise temperature control, stable release of aerosol components, and sensitive response while improving the lifespan of the heating element, but also meet the structural characteristics requirements of small heating elements. The performance advantages of the heating element include: rapid heating rate (reaching 300°C within 5 seconds after power-on); high temperature control accuracy (fluctuation < ±2°C under PID algorithm feedback); and long service life (resistance change rate < 3% after 1000 cycles of heating). Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the structure of the graphene-metal nanoparticle composite sheet heating element provided in Embodiment 1 of the present invention; Figure 2 This is a schematic diagram of the structure of a cigarette heating device using a central plate heating element provided in Embodiment 1 of the present invention; Figure 3 This is a schematic diagram of the structure of the viscose-based carbon fiber Co nanoparticle composite conductive needle provided in Embodiment 5 of the present invention; Figure 4 This is a schematic diagram of the structure of a cigarette heating device using a central needle-type heating element provided in Embodiment 5 of the present invention; Figure 5 This is a schematic diagram of the structure of the vapor-grown carbon fiber Zr nanoparticle composite conductive ring provided in Embodiment 6 of the present invention; Figure 6 This is a schematic diagram of the structure of the cigarette heating device with a circumferential heating element provided in Embodiment 3 of the present invention. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0028] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0029] In this invention, unless otherwise specified and / or stated, all numerical values involving component amounts are "by weight". Unless otherwise specified, the terminology used in this invention are common terms in the relevant field. Unless otherwise specified, the preparation processes, testing methods, etc., used in the various embodiments are conventional methods well known to those skilled in the art, and the raw materials and equipment used can be obtained from publicly available commercial sources.
[0030] The specific embodiments of the present invention adopt the following technical solutions: I. Carbon-based composite conductive materials and their preparation methods First, the carbon-based conductive composite network structure material is pre-oxidized in a mixed atmosphere at 180 ℃ to 320 ℃ for 2 h to 5 h. Then, it is impregnated in a metal salt solution with a concentration of 2% to 50%. Under an inert gas environment, the metal salt is reduced at 180 ℃ to 450 ℃ for 1 h to 3 h, generating metal nanoparticles in the carbon-based conductive composite network structure material. This yields a carbon-based conductive composite material modified with metal nanoparticles. The filling degree of the metal nanoparticles in the carbon-based conductive composite network structure material is 5% to 50%, such as 5%, 10%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., preferably 18% to 40%.
[0031] The pre-oxidation temperature can be 180℃, 200℃, 230℃, 250℃, 270℃, 280℃, 300℃, 320℃, etc., preferably 250℃~320℃; the pre-oxidation time is preferably 3~5 h. The reduction reaction temperature can be 180℃, 200℃, 220℃, 250℃, 280℃, 300℃, 350℃, 380℃, 400℃, 420℃, 430℃, 450℃, etc., preferably 280℃~450℃. The mixed atmosphere mainly consists of oxygen and nitrogen, and the oxygen volume percentage is 10~25%, such as 10%, 15%, 20%, 25%, etc. The carbon-based conductive composite material can be a film, or a sheet or needle-like material made by laminating and pressing a film.
[0032] II. Laser Sintering Bonding First, the thermally conductive insulating layer material is deposited layer by layer onto the surface of the carbon-based composite conductive material using static pressing, dry pressing, or photopolymerization 3D printing. Then, interlayer laser sintering is performed at 1200 ℃~1500 ℃ for 15 min~90 min to obtain a sintered body of the thermally conductive core layer and the thermally conductive insulating layer. The laser sintering temperature can be 1200 ℃, 1250 ℃, 1300 ℃, 1350 ℃, 1400 ℃, 1450 ℃, 1500 ℃, etc.; the laser sintering time can be 15 min, 30 min, 45 min, 60 min, 75 min, 90 min, etc.
[0033] III. Formation of Interfacial Coating An interface coating is formed on the outer surface of the conductive core layer and the thermally conductive insulating layer by methods such as magnetron sputtering, plasma spraying, or dip coating. A Pt100 temperature sensor and a PID control circuit are integrated on the interface coating to produce a heating element with dimensions of 40 mm × 0.35 mm × 0.1 mm. The thickness of the thermally conductive insulating layer in the heating element is preferably 0.5 µm to 2 µm, such as 0.5 µm, 0.8 µm, 1 µm, 1.2 µm, 1.4 µm, 1.5 µm, 1.6 µm, 1.8 µm, 2 µm, etc.; the thickness of the interface coating is preferably 0.05 µm to 2 µm, such as 0.05 µm, 0.1 µm, 0.2 µm, 0.3 µm, 0.4 µm, 0.5 µm, 0.8 µm, 1 µm, 1.2 µm, 1.4 µm, 1.5 µm, 1.6 µm, 1.8 µm, 2 µm, etc.
[0034] IV. Application in Smoking Accessories The heating element described above is installed in a heated cigarette device, which includes a heating chamber filled with 0.9 g of tobacco aroma-releasing material, and the heating element is installed at its center. The tobacco aroma-releasing material is primarily reconstituted tobacco leaf shreds, and its key components consist of nicotine, flavor components, and glycerin.
[0035] The main materials used in the following embodiments and comparative examples are as follows: Graphene filmThe graphene has a network structure and is prepared by the following method: 600 g of graphite powder with a particle size of 3-20 μm is added to 2100 ml of 98% concentrated sulfuric acid and stirred until homogeneous. 180 g of potassium permanganate is slowly added under water bath conditions, controlling the temperature not to exceed 20 °C to prevent excessively vigorous reaction. After the reaction is complete, deionized water is added, and the reaction system is heated to 98 °C and the reaction continues for 30 minutes. 110 ml of 30% hydrogen peroxide is added to remove excess potassium permanganate, and the reaction system turns bright yellow. The system is washed repeatedly with deionized water and dilute hydrochloric acid until the pH is close to neutral. Finally, the graphene is dispersed by ultrasonication to obtain an oxidized graphene dispersion. The graphene dispersion is then filtered to obtain a filtered graphene membrane with a porosity of 34.1%, an electrical conductivity of 2556 S / cm, and a thermal conductivity of 44.79 W / (m·K).
[0036] Tobacco aroma-releasing raw material: The raw material is prepared by soaking tobacco stem fibers in a mixture of tobacco extract (45% solids content) 50g, tobacco powder 12g, glycerin 8g, and propylene glycol 2g. The mixture is soaked for 30 seconds and then dried.
[0037] The methods for measuring aerosol release rate in the following embodiments and comparative examples : A high-throughput aerosol particle trap (MAC600A) was used to simulate smoking tests using a smoking device. Test conditions: HCl (deep smoking mode); sinusoidal flow curve; sampling volume 55 ml; sampling time 2 s; sampling interval 30 s; preheating time 30 s; 8 samplings per sample. The samples before and after heating were immersed in 35 mL of isopropanol extractant, and the sample residue was immersed in 35 mL of methanol extractant. The samples were shaken for 3 h and allowed to stand for 12 h to complete the chromatographic analysis. The release of key components before and after heating was tested using a gas chromatograph (HP6890). Analytical methods: Column: HP-INNOWAX capillary column (30 m × 0.32 mm × 0.25 µm); Temperature program: 60 ℃ (5 min) 10 ℃ / min 150 ℃ (1 min) 2 ℃ / min 180 ℃ (0.5 min) 20 ℃ / min 240 ℃ (1 min). Injection volume: 1 µL; split ratio: 5:1; inlet temperature: 250 ℃; detector temperature: 260 ℃; carrier gas: helium (≥99.999%); flow rate: 2.0 mL / min; reference flow rate: 20 mL / min; make-up gas flow rate: 9 mL / min.
[0038] The release rate (P, %) of the key component is calculated according to formula (1): P = (m0 - m1) / m0 × 100 (1) In the formula: m0 is the initial content of the key component of the sample, mg / cm³.2 m1 represents the content of the key residual components in the sample after heating, in mg / cm³. 2 .
[0039] Example 1 This embodiment provides a heating element, its preparation method, and its application, as detailed below: I. Graphene-Chromium Nanoparticle Conductive Composite Materials First, the graphene film was pre-oxidized in a mixed atmosphere at 300 °C for 4 h, and then impregnated in a 5% chromium nitrate solution. Under an argon atmosphere, the chromium nitrate was reduced at 280 °C for 2 h to generate chromium nanoparticles on the graphene surface, thus obtaining a graphene conductive composite material modified with chromium nanoparticles. The filling degree of the chromium nanoparticles in the graphene film was 8%. The thermal conductivity of the graphene conductive composite material was 45.13 W / (m·K), the electrical conductivity was 17765.7 S / cm, and the oxygen volume ratio in the mixed atmosphere was 20%.
[0040] II. Laser Sintering Bonding A layer-by-layer deposition of aluminum nitride (AlN) onto a graphene conductive composite sheet modified with chromium nanoparticles was employed using isostatic pressing (OSP). The layers were then bonded by laser sintering to obtain a sintered sheet of graphene conductive composite material modified with chromium nanoparticles and AlN. The AlN layer thickness was 1 µm. The OSP process parameters were as follows: AlN powder with a particle size of 0.75 µm was filled into the isostatic press mold; pressure was applied at 250 MPa / 20°C; pressure was held for 60 s; and the sheet was demolded and allowed to stand for 20 min. The sintering conditions included a temperature of 1300°C and a time of 45 min.
[0041] III. Formation of Interfacial Coating A 0.35 µm thick Al₂O₃ coating was applied to the outer surface of the graphene conductive composite sheet modified with chromium nanoparticles and the sintered AlN sheet obtained in step two using plasma spraying technology. A Pt₁₀₀ temperature sensor and a PID control circuit were integrated to produce a sheet with dimensions of 40 mm × 0.35 mm × 0.1 mm. Figure 1 The graphene-metal nanoparticle composite sheet heating element 10 shown includes a conductive core layer 12 composed of a graphene conductive composite material modified with chromium nanoparticles at the center, an AlN thermally conductive insulating layer 14 surrounding the conductive core layer 12, and an Al2O3 interface coating 16 located on the outermost layer and surrounding the AlN thermally conductive insulating layer 14. The plasma spraying process parameters are as follows: vacuum level of the ion sputtering instrument set to 3 Pa, sputtering voltage 400 V, sputtering current 20 mA, time 30 s, and target-sample distance 20 mm.
[0042] IV. Application in Smoking Accessories Install the heating element 10 as described above. Figure 2 The heated cigarette device shown includes a device body 20, a heating chamber 30 formed by the device body 20, 0.9 g of tobacco aroma release material filled in the heating chamber 30, and the aforementioned heating element 10 installed at its center.
[0043] Example 2 This embodiment is basically the same as Example 1, with the main difference being: the graphene film is first pre-oxidized at 300 °C for 4 h, then immersed in a 17% nickel nitrate solution, and the nickel nitrate is reduced at 320 °C for 2 h under argon atmosphere, generating nickel nanoparticles on the graphene surface to obtain a nickel nanoparticle-modified graphene conductive composite material, with the chromium nanoparticles filling 21.6% of the graphene film; the thermal conductivity of this graphene conductive composite material is 47.41 W / (m·K), and the electrical conductivity is 17529 S / cm. Other steps and operations are the same.
[0044] Example 3 This embodiment is basically the same as Embodiment 1, with the main difference being: In this embodiment, the graphene film is first pre-oxidized at 300 °C for 4 h, then immersed in a 35% silver nitrate solution, and the silver nitrate is reduced at 450 °C for 2 h under argon atmosphere to generate silver nanoparticles on the graphene surface, thus obtaining a graphene conductive composite material modified with silver nanoparticles. The filling degree of the chromium nanoparticles in the graphene film is 28.4%. The thermal conductivity of this graphene conductive composite material is 58.72 W / (m·K), and the electrical conductivity is 21276.93 S / cm. Other steps and operations are the same.
[0045] Comparative Example 1 This comparative example is basically the same as Example 1, except that: in this comparative example, a graphene film is used directly as the conductive core layer to replace the graphene conductive composite sheet modified with metal nanoparticles. Other steps and operations are the same.
[0046] Comparative Example 2 This comparative example is basically the same as Example 1, except that: this comparative example uses a nickel-chromium alloy heating element, which is used in traditional heated cigarette devices, instead of the graphene metal nanoparticle composite sheet heating element provided in Example 1, and uses electroplated chromium as an anti-oxidation surface. Other steps and operations are the same.
[0047] Detection The heating cigarette devices provided in Examples 1-3 and Comparative Examples 1-2 were tested by inputting a voltage of 5V and a current of 2A to a heating area of φ10 mm × 5 mm.
[0048] The test items included: time to heat up to 300℃, steady-state temperature fluctuation (300℃ cyclic heating 8 times), resistivity change after 300℃ cyclic heating 1000 times, and aerosol release rate. The results are shown in Table 1.
[0049] Table 1. Detection results of Examples 1-3 and Comparative Examples 1-2
[0050] Table 1 shows that, compared to a single graphene film (Comparative Example 1), the composite conductive material prepared by modifying the graphene film with metal nanoparticles exhibits a 2-second reduction in the time required to heat to 300 °C, lower temperature control accuracy, a 4% decrease in resistance change rate after 1000 cycles, and an increase of over 10% in aerosol release. Compared to Comparative Example 2, the performance of Examples 1-3 is significantly enhanced. Therefore, the metal nanoparticle-modified graphene conductive composite material and heating element provided by the embodiments of this invention can achieve efficient heating using the Joule heating effect while meeting the requirements for energy saving and consumption reduction during the heating process.
[0051] Based on resistivity tests, Comparative Example 2, which uses a nickel-chromium alloy as the heating element in traditional heated cigarette devices and employs electroplated chromium as the anti-oxidation surface, shows that the anti-oxidation interface coatings used in Examples 1-3 have similar room-temperature anti-oxidation capabilities to the electroplated chromium material, effectively preventing the oxidation of metal materials. However, when the heating temperature reaches 300℃, an oxide layer gradually forms on the chromium oxide surface of the heating element in Comparative Example 2, with the chromium-nickel alloy element exhibiting a resistance change rate of <8% after 1000 cycles of heating. In contrast, the interface coating material in Examples 1-3 of this invention has an anti-oxidation temperature ≥400℃ and effectively protects the core layer of the heating element during use, with the heating element exhibiting a resistance change rate of <3% after 1000 cycles of heating.
[0052] Example 4 This embodiment provides a heating element, its preparation method, and its application, as detailed below: Step 1: Ag nanoparticle-modified pitch-based carbon fiber network material First, pitch-based carbon fiber material with a porosity of 45% and an electrical conductivity of 15200 S / cm was pre-oxidized in a mixed atmosphere at 250 °C for 5 h. Then, it was impregnated in a 25% AgNO3 solution and reduced in helium at 450 °C for 3 h to generate a pitch-based carbon fiber network material modified with Ag nanoparticles with a filling degree of 35.9% and a size of 40 mm × 2.5 mm × 0.25 mm. The oxygen volume ratio in the mixed atmosphere was 15%.
[0053] Step 2: Laser Sintering Bonding Aluminum nitride (AlN) was deposited layer-by-layer onto an Ag nanoparticle-modified pitch-based carbon fiber network material using isostatic pressing (ABS) technology, with interlayer bonding achieved via laser sintering. The ABS process parameters were as follows: the isostatic press mold was filled with 0.75 µm aluminum nitride (AlN) powder; pressure was applied at 250 MPa / 20°C; pressure was held for 60 s; and the material was demolded and allowed to stand for 20 min. The laser sintering conditions included a temperature of 1200°C and a laser sintering time of 45 min.
[0054] Step 3: Forming an interface coating A 35 µm thick Al2O3 coating was applied to the surface of the material obtained in step two using plasma spraying technology. A Pt100 temperature sensor and PID control circuit were integrated to obtain a pitch-based carbon fiber silver nanoparticle composite sheet with dimensions of 41 mm × 3 mm × 0.8 mm. The plasma spraying process parameters were as follows: vacuum level of the ion sputtering instrument set to 3 Pa, sputtering voltage 400 V, sputtering current 20 mA, time 30 s, and target-sample distance 20 mm.
[0055] Step 4: Application in Smoking Accessories The pitch-based carbon fiber silver nanoparticle composite sheet obtained in step three is installed onto... Figure 2 The heated cigarette device shown.
[0056] Comparative Example 3 This comparative example is basically the same as Example 4, except that: in this comparative example, pitch-based carbon fiber material is used directly as the conductive core layer to replace the pitch-based carbon fiber network material modified with Ag nanoparticles. Other steps and operations are the same.
[0057] Comparative Example 4 This comparative example is basically the same as Example 4, except that: in this comparative example, a nickel-chromium alloy heating element is used instead of the pitch-based carbon fiber silver nanoparticle composite sheet provided in Example 4, and electroplated chromium is used as the anti-oxidation surface. Other steps and operations are the same.
[0058] test The heated cigarette devices provided in Example 4 and Comparative Examples 3-4 were tested with an input voltage of 5V and a current of 2A, and a heating area of φ10mm×5mm. The test items included: time to heat up to 300℃, steady-state temperature fluctuation (300℃ cyclic heating 8 times), resistivity change after 1000 cycles of 300℃ heating, and aerosol release rate. The results are shown in Table 2.
[0059] Table 2. Detection results of Example 4 and Comparative Example 3
[0060] Compared to Comparative Example 3, the time required to heat to 300 °C in Example 4 was increased by nearly 2 seconds, and the temperature accuracy was improved by more than 1 °C. Compared to Comparative Example 4, the time required to heat to 300 °C in Example 4 was increased by more than 10 seconds, and the temperature accuracy was improved by more than 3 °C. Compared to Comparative Examples 3-4, the resistivity change rate of Example 4 was reduced by 3%, and the stability of aerosol release was improved by 16%. Therefore, the Ag nanoparticle-modified pitch-based carbon fiber network material and heating element provided by the embodiments of the present invention can achieve efficient heating by utilizing the Joule heating effect while meeting the requirements of precise temperature control and energy saving during the heating process, and the aerosol release is stably improved.
[0061] Example 5 This embodiment provides a heating element, its preparation method, and its application, as detailed below: Step 1: Co nanoparticle-modified viscose-based carbon fiber network material First, viscose-based carbon fiber material with a porosity of 39% and a conductivity of 21800 S / cm was pre-oxidized in air at 300 °C for 4 h. Then, it was impregnated in a 20% Co(CH3COO)2 solution and reduced under argon atmosphere at 180 °C for 2 h to generate a Co nanoparticle-modified viscose-based carbon fiber network membrane with a filling degree of 27.5%. The Co nanoparticle-modified viscose-based carbon fiber network membrane was then processed by convolution pressing to form a needle-like structure with a size of φ1.5 mm × 60 mm.
[0062] Step 2: Laser Sintering Bonding A photopolymer 3D printing technique was used to deposit magnesium oxide partially stabilized zirconium oxide (Mg-PSZ) layer by layer into a Co nanoparticle-modified viscose-based carbon fiber network material, with interlayer bonding via laser sintering. The sintering temperature was 1350℃, and the laser sintering time was 45 min. The photopolymer 3D printing process parameters were as follows: the printer was filled with 0.6 µm particle size magnesium oxide partially stabilized zirconium oxide (Mg-PSZ) powder with a printing precision of 0.075 mm; the light intensity was set to 10 mW / cm²; the exposure time was 15 s; the layer thickness was 0.075 mm; and the printing speed was 50 mm / s.
[0063] III. Formation of Interfacial Coating A 45 µm thick AlN coating was applied to the outer surface of the material obtained in step two using magnetron sputtering. A Pt100 temperature sensor and PID control circuit were integrated to obtain a material with dimensions of φ1.65 mm × 63 mm. Figure 3The viscose-based carbon fiber Co nanoparticle composite conductive needle 40 shown comprises a conductive core layer 42 composed of a viscose-based carbon fiber network material modified with Co nanoparticles at the center, a Mg-PSZ thermally conductive insulating layer 44 enclosing the conductive core layer 42, and an AlN interface coating 46 located on the outermost layer and enclosing the Mg-PSZ thermally conductive insulating layer 44. The magnetron sputtering process parameters are as follows: the vacuum degree of the magnetron sputtering instrument is set to 10... -3 Pa, sputtering power 150 W, selected radio frequency (RF) sputtering mode, working gas pressure 0.5 Pa, argon flow rate 10 sccm, target-sample distance 50 mm.
[0064] IV. Application in Smoking Accessories The heating element viscose-based carbon fiber Co nanoparticle composite conductive needle 40 prepared in step three is installed onto... Figure 4 The heated cigarette device shown includes a device body 20, a heating cavity 30 formed by the device body 20, 0.95g of tobacco aroma release material filled in the heating cavity 30, and the aforementioned viscose-based carbon fiber Co nanoparticle composite conductive needle 40 installed at its center.
[0065] Comparative Example 5 This comparative example is basically the same as Example 5, except that: in this comparative example, viscose-based carbon fiber material is used directly as the conductive core layer to replace the viscose-based carbon fiber network material modified with Co nanoparticles. Other steps and operations are the same.
[0066] Comparative Example 6 This comparative example is basically the same as Example 5, except that: this comparative example uses a nickel-chromium alloy heating needle of the same specification instead of the viscose-based carbon fiber Co nanoparticle composite conductive needle provided in Example 6, and uses electroplated chromium as an anti-oxidation surface. Other steps and operations are the same.
[0067] test The heated cigarette devices provided in Examples 5 and Comparative Examples 5-6 were tested with an input voltage of 4.5V and a current of 1.2A, and a heating area of φ2.5 mm × 10 mm. The test items included: time to heat up to 300℃, steady-state temperature fluctuation (8 cycles of heating at 300℃), resistivity change after 1000 cycles of heating at 300℃, and aerosol release rate. The results are shown in Table 3.
[0068] Table 3. Detection results of Example 5 and Comparative Examples 5-6
[0069] Compared with Comparative Example 5, the time required to heat to 300 °C in Example 5 was significantly shortened, the temperature control accuracy was significantly reduced, and the resistance change rate remained basically unchanged. Compared with Comparative Example 6, the time required to heat to 300 °C in Example 5 was increased by nearly 10 seconds, the temperature accuracy was improved by more than 2.5 °C, and the resistance change rate was reduced by 4%. Compared with Comparative Examples 3-4, the stability of aerosol release in Example 4 was improved by more than 13%. Therefore, the Co nanoparticle-modified viscose-based carbon fiber network material and heating element provided by the embodiments of the present invention can achieve efficient heating by utilizing the Joule heating effect while meeting the requirements of precise temperature control and energy saving during the heating process, and the aerosol release is stably improved.
[0070] Example 6 This embodiment provides a heating element, its preparation method, and its application, as detailed below: Step 1: Zr nanoparticle-modified vapor-grown carbon fiber network material First, a vapor-grown carbon fiber material with a porosity of 33% and an electrical conductivity of 16800 S / cm was pre-oxidized in a mixed atmosphere at 200 °C for 4 h. Then, it was impregnated in a 12% Zr(NO3)4 solution and reduced at 205 °C for 2.4 h under argon atmosphere to generate a Zr nanoparticle-modified vapor-grown carbon fiber network material with a filling density of 24.6%. This material has a ring structure with an inner diameter of 7.5 mm, an outer diameter of 9 mm, and a length of 90 mm. The oxygen volume ratio in the mixed atmosphere was 25%.
[0071] II. Laser Sintering Bonding Silicon nitride (Si3N4) was deposited layer by layer onto a vapor-grown carbon fiber network material using dry pressing technology, with interlayer bonding achieved via laser sintering. The laser sintering temperature was 1280 ℃, and the laser sintering time was 60 min. The dry pressing process parameters were as follows: the dry pressing machine was filled with 0.5 µm Si3N4 powder, subjected to bidirectional pressure of 100 MPa, held for 30 s, and then demolded and allowed to stand for 30 min.
[0072] III. Formation of Interfacial Coating A 21 µm thick graphene coating was applied to the surface of the material obtained in step two using an impregnation coating technique. A Pt100 temperature sensor and a PID control circuit were integrated to obtain a material with an inner diameter of 7.7 mm, an outer diameter of 9.2 mm, and a length of 90.2 mm. Figure 5The vapor-grown carbon fiber Zr nanoparticle composite conductive ring 50 shown comprises an innermost annular conductive core layer 52 composed of a Zr nanoparticle-modified vapor-grown carbon fiber network material, a Si3N4 thermally conductive insulating layer 54 enclosing the conductive core layer 52, and an outermost graphene interface coating 56 enclosing the Si3N4 thermally conductive insulating layer 44. The impregnation coating process parameters are: 50 wt% graphene coating dispersion, impregnation speed of the impregnation coating machine 1 m / min, and infrared drying temperature of 80 °C.
[0073] IV. Application in Smoking Accessories The vapor-grown carbon fiber Zr nanoparticle composite conductive ring 50 prepared in step three is installed onto... Figure 6 The heated cigarette device shown includes a device body 20, a heating cavity 30 formed by the device body 20, a vapor-grown carbon fiber Zr nanoparticle composite conductive ring 50 installed on the inner wall of the heating cavity 30, and 0.95 g of tobacco aroma release raw material filled in the inner cavity of the vapor-grown carbon fiber Zr nanoparticle composite conductive ring 50.
[0074] Comparative Example 7 This comparative example is basically the same as Example 6, except that: in this comparative example, vapor-grown carbon fiber network material is used directly as the conductive core layer instead of the Zr nanoparticle-modified vapor-grown carbon fiber network material. Other steps and operations are the same.
[0075] Comparative Example 8 This comparative example is basically the same as Example 6, except that: in this comparative example, a nickel-chromium alloy heating ring of the same specification is used instead of the vapor-grown carbon fiber Zr nanoparticle composite conductive ring provided in Example 6, and electroplated chromium is used as the anti-oxidation surface. Other steps and operations are the same.
[0076] test The heated cigarette devices provided in Examples 6 and 7-8 were input with a voltage of 5V and a current of 1.5A, and circumferential heating was performed. The heating cup area was φ7.2mm×10mm. The test items included: time to heat up to 300℃, steady-state temperature fluctuation (300℃ cyclic heating 8 times), resistivity change after 1000 cycles of 300℃ heating, aerosol release rate, etc. The results are shown in Table 4.
[0077] Table 4. Detection results of Example 6 and Comparative Examples 7-8
[0078] Compared to Comparative Example 7, Example 6 showed an improvement in heating time to 300 °C by more than 2 seconds, an increase in temperature accuracy of nearly 1 °C, a decrease in resistance change rate of 1%, and an improvement in aerosol release stability of 6%. Compared to Comparative Example 8, Example 6 showed an improvement in heating time to 300 °C by more than 10 seconds, an increase in temperature accuracy of 1.8 °C, a decrease in resistance change rate of 3%, and an improvement in aerosol release stability of 13%. Therefore, the Zr nanoparticle-modified vapor-grown carbon fiber network material and heating element provided by the embodiments of the present invention can achieve efficient heating by utilizing the Joule heating effect while meeting the requirements of precise temperature control and energy saving during the heating process, and the aerosol release is stably improved.
[0079] In summary, the carbon-based composite conductive material, heating element, and heated cigarette device provided in the embodiments of the present invention achieve rapid heating, precise temperature control, stable release of aerosol components, and sensitive response, while improving the service life of the heating element and better meeting the structural characteristics requirements of small heating elements. Specifically, the processed element reaches 300°C within 5 seconds after being energized, with fluctuations of <±2°C under PID algorithm feedback, a resistance change rate of <3% after 1000 cycles of heating, and an aerosol component release rate exceeding 90%. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it; although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications can still be made to the specific implementation methods of the present invention or equivalent substitutions can be made to some technical features without departing from the spirit of the technical solutions of the present invention, and all such modifications should be covered within the scope of the technical solutions claimed in the present invention.
Claims
1. A method for preparing a carbon-based composite conductive material, comprising the steps of: firstly pre-oxidizing the carbon-based conductive composite network structure material; then immersing it in a metal salt solution and reducing it in situ under an inert gas environment to form metal nanoparticles, thereby obtaining a carbon-based conductive composite material modified with metal nanoparticles.
2. The preparation method according to claim 1, characterized in that, The pre-oxidation treatment step includes: pre-oxidizing the carbon-based conductive composite network structure material in a mixed atmosphere at 180℃~320℃ for 2 h~5 h; wherein the mixed atmosphere is mainly composed of oxygen and nitrogen, and the volume percentage of oxygen in the mixed atmosphere is 10~25%.
3. The preparation method according to claim 1, characterized in that, The carbon-based conductive composite network architecture material has a porosity of 0.5% to 50% and a conductivity of 1000 S / cm to 100000 S / cm.
4. The preparation method according to any one of claims 1-3, characterized in that, The concentration of the metal salt solution is 2wt% to 50wt%, the impregnation time is 0.5 to 6 h, and the filling degree of the metal nanoparticles in the carbon-based conductive composite network structure material is 5% to 50%.
5. The preparation method according to claim 1, characterized in that, The metal salt solution also contains a soluble salt of at least one of the following metals: Ag, Cu, Al, Ni, Zn, Ti, Co, Rh, Pt, Fe, Pd, Zr.
6. The preparation method according to claim 1, characterized in that, The in-situ reduction reaction temperature is 180 ℃~450 ℃, and the in-situ reduction reaction time is 1 h~3 h.
7. The preparation method according to claim 1, characterized in that, The carbon-based conductive composite network architecture material includes one or more porous materials with a three-dimensional network structure, such as multilayer graphene, carbon fiber, and carbon nanotubes.
8. The preparation method according to claim 7, characterized in that, The carbon fiber is pitch-based carbon fiber material, viscose-based carbon fiber material, or vapor-grown carbon fiber material.
9. The preparation method according to claim 7, characterized in that, The carbon-based conductive composite network structure material is a graphene self-supporting membrane with a porosity of 30% to 50%, which is mainly prepared by filtration of graphene dispersion; the filling degree of the metal nanoparticles in the graphene self-supporting membrane is 21.6% to 28.4%.
10. A carbon-based composite conductive material prepared by the preparation method according to any one of claims 1-9.
11. A heating element based on the Joule heating effect, characterized in that, include: The conductive core layer can convert electrical energy into heat energy, and the thermally conductive insulating layer can isolate the conductive core layer from the external environment, wherein the conductive core layer is composed of the carbon-based composite conductive material as described in claim 10.
12. The heating element according to claim 11, characterized in that, The material of the thermally conductive insulating layer includes one or more of carbon-based ceramic materials, nitrogen-based ceramic materials, and boron-based ceramic materials.
13. The heating element according to claim 12, characterized in that, The thermally conductive insulating layer is made of hexagonal boron nitride, aluminum nitride, or silicon nitride.
14. The heating element according to claim 11, 12, or 13, characterized in that, The thickness of the thermally conductive insulating layer is 0.5 µm to 2 µm.
15. The heating element according to claim 11, 12, or 13, characterized in that, It also includes an interface coating to suppress thermal stress peeling between the conductive core layer and the thermally conductive insulating layer.
16. The heating element according to claim 15, characterized in that, The interface coating includes any single layer or any composite coating selected from Al2O3 coating, AlN coating, BN coating, and graphene coating.
17. The heating element according to claim 15, characterized in that, The interface coating integrates a Pt100 temperature sensor and a PID control circuit, and the Pt100 temperature sensor and the PID control circuit are electrically connected to the conductive core layer, respectively.
18. The heating element according to claim 17, characterized in that, The thickness of the interface coating is 0.05 µm to 2 µm.
19. The heating element according to claim 11, characterized in that, The heating element has a ring-shaped, sheet-shaped, or needle-shaped morphology.
20. A method for preparing a heating element according to any one of claims 11-19, comprising the steps of: laminating or co-firing the thermally conductive insulating layer onto the conductive core layer, wherein the layers are bonded by laser sintering.
21. The preparation method according to claim 20, characterized in that, First, the thermally conductive insulating layer material is deposited layer by layer onto the surface of the carbon-based composite conductive material using static pressing, dry pressing, or photopolymerization 3D printing, and then interlayer laser sintering is performed.
22. The preparation method according to claim 21, characterized in that, The laser sintering temperature is 1200 ℃~1500 ℃, and the laser sintering time is 15 min~90 min.
23. The preparation method according to any one of claims 20-22, characterized in that, It also includes forming an interface coating on the outer surface of the conductive core layer and the thermally conductive insulating layer using magnetron sputtering, plasma spraying, or dip coating methods.
24. The preparation method according to claim 23, characterized in that, It also includes: integrating a Pt100 temperature sensor and a PID control circuit on the surface of the interface coating.
25. The use of a heating element according to any one of claims 11-19 in a tobacco product heater or smoking device.
26. The application according to claim 25, characterized in that, The heating device or smoking device is a new type of heating device or smoking device for tobacco products.
27. The application according to claim 26, characterized in that, The heating element can be heated in the following ways: central plate heating, central needle heating, or annular circumferential heating.
28. A heated cigarette smoking device, characterized in that, It includes a heating chamber and a heating element as described in any one of claims 11-19, which is installed in the heating chamber.
29. The heated cigarette smoking device according to claim 28, characterized in that, The heating chamber is filled with tobacco aroma-releasing raw materials and is in direct contact with the heating element.
30. The application of the carbon-based composite conductive material of claim 10 or the heating element of any one of claims 11-19 in heating cigarettes.